A Study about Urban Design Schemes: Walled City of Nicosia - Bolkaner, Mine Kuset; Asilsoy, Buket; Uzunoğlu, Semra Sema (European Journal of Sustainable Development, 2020)
Historical neighbourhoods are among the most significant indicators of the cities; as they involve history, culture, architecture and social life. It is very important to protect and ensure sustainability of these places. This goal needs to be achieved without damaging the urban identity via protecting the historic entities. Additionally the restoration and re-use works need to take place under the supervision and cooperation of related government bodies and civil society organisations. Nicosia with its Walled City is a historical environment with a rich architectural and cultural heritage that is currently the focal point of conservation and rehabilitation activities as a circle of urban design implementations. Within this framework in this study, the aim is to evaluate perception and views of the users about urban design implementations involving rehabilitation and conservation activities via survey. Based on the results, the users seemed satisfied with the outcomes of the rehabilitation and re-use of the buildings. However the participants also highlighted the existence of car parking problems, inadequate infrastructure and urban furniture and environmental pollution. Additionally the users do not prefer the areas that have not been renovated and the regions with low socio-cultural characteristics. Keywords: Historical environment; urban design; user perception; Nicosia Walled City